"THE POSITIVE EFFECTS OF USING VERMICOMPOST ON THE GROWTH AND DEVELOPMENT OF CROPS" (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Vermicompost, also known as vermicompost, is a product of the decomposition process using various worms such as red worms, white worms and other worms. It is usually produced by the decomposition of organic plant or food waste in combination with worm castings produced by red worms, white worms and other compost worms. Vermicompost is a nutrient-rich organic fertilizer that is beneficial for soil health and plant growth. It is a sustainable and environmentally friendly alternative to chemical fertilizers that improves soil fertility and increases crop yields. This article provides information on the positive effects of using vermicompost on crop growth and development.